The effects of cardiac rehabilitation on haemodynamic parameters measured by impedance cardiography in patients with coronary artery disease - Stojanović Milovan; Deljanin-Ilić Marina; Ilić Stevan; Petrović Dejan; Ilić Bojan (Vojnosanitetski Pregled)
Background/Aim. Well-organized cardiovascular rehabilitation (CVR) reduces cardiovascular burden by influencing cardiovascular risk factors, improving the quality of life, and reducing mortality and hospital readmission. However, its effects on hemodynamic status are largely unknown. The aim of our study was to evaluate the influence of a three-week CVR program on hemodynamic status and to investigate if there is a correlation between physical strain tolerance and hemodynamic parameters measured by impedance cardiography (ICG) before and after the CVR program in patients with coronary artery disease (CAD). Methods. Fifty-two patients attended a three-week CVR program. At the beginning and the end of the rehabilitation program, laboratory tests, exercise stress tests (EST), and ICG measurements were taken. Results. Patients showed better strain tolerance on the second exercise stress test (EST2) by achieving a higher strain level (Z = 2.315; p = 0.021) and a longer duration of the test (Z = 2.305; p = 0.021). There was a strong positive correlation between the level of EST2 and cardiac output (CO) (r = 0.538; p < 0.001) and stroke volume (SV) (r = 0.380; p = 0.017) on the second ICG (ICG2). Moreover, there was a strong negative correlation between EST2 level and systemic vascular resistance (SVR) (r = -0.472; p = 0.002) and SVR index (SSVRI) (r = -0,407; p = 0.010) on ICG2. There was a strong positive correlation between EST2 duration and CO (r = 0.517; p = 0.001) as well as between EST2 duration and SV (r = 0.340; p = 0.034), and a strong negative correlation between EST2 duration and SVR (r = -0.504; p = 0.001) as well as between EST2 duration and SVRI (r = -0.448; p = 0.004), according to ICG2. Conclusion. Our study showed that a well-designed CVR program can lead to better physical strain tolerance in patients with CAD. Furthermore, CVR led to a significant positive correlation between EST and CO as well as between EST and SV measured by ICG. On the other hand, there was a significant negative correlation between EST and vascular-related parameters according to ICG at the end of the CVR program.